Analisis Pembelajaran IPA pada Materi Abiotik dan Biotik Melalui Pemanfaatan Lingkungan Sekitar - Lia Fafina Salsabilah; Enik Setiawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze science learning on abiotic and biotic materials through the utilization of the surrounding environment and students’ understanding of the material. This research employed a descriptive qualitative approach with the subjects consisting of a teacher and fifth-grade students of SD Kedungturi. Data were collected through observation, interviews, and documentation. The results showed that environment-based learning was implemented through direct observation, discussion, and reflection activities. These activities helped students identify, differentiate, and understand the relationships between abiotic and biotic components. Therefore, the utilization of the surrounding environment provides more concrete and meaningful learning experiences for students.